2001
DOI: 10.1046/j.1440-1746.2001.02514.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and splanchnic hemodynamics following hemorrhage and volume restitution with Haemaccel in portal hypertensive rats: The effect of propranolol

Abstract: In this model, pretreatment with propranolol prevented the increase in portal venous inflow, which occurs following hemorrhage and volume restitution with Haemaccel. Although caution should be taken in extrapolating data from animal models to humans, our results suggest that volume replacement during a portal hypertensive-related bleeding episode may be safer in a patient treated with non-selective beta-adrenoreceptor antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Villanueva et al 15 showed that liberal blood transfusion leads to worse outcomes in a RCT of 921 patients with upper GI bleeding, which was supported by prior animal model studies that showed increased portal pressure and impaired coagulation with blood transfusion. 16,17 However, no such high-quality evidence exists for the role of platelet transfusion in GI bleeding. The authors cite a prior retrospective study from the cardiac surgery literature, which showed that patients who received platelet transfusion had a significantly higher risk of death after propensity score matching.…”
mentioning
confidence: 99%
“…Villanueva et al 15 showed that liberal blood transfusion leads to worse outcomes in a RCT of 921 patients with upper GI bleeding, which was supported by prior animal model studies that showed increased portal pressure and impaired coagulation with blood transfusion. 16,17 However, no such high-quality evidence exists for the role of platelet transfusion in GI bleeding. The authors cite a prior retrospective study from the cardiac surgery literature, which showed that patients who received platelet transfusion had a significantly higher risk of death after propensity score matching.…”
mentioning
confidence: 99%